The Psychometric Aspects of Adolescents\' Attitude Scale toward Addiction - Hassan Rafiei; Ali Reza Jazayeri; Mohammad Ali Nazari; Leila Soleimani-Nia (Journal of Rehabilitation, 2007)
Objective: Attitude modification is a known way in substance abuse prevention. in order to assessment of adolescents, attitude toward addiction, addict and drugs, and evaluation of their changes caused by preventive interventions , a scale was designed and its psychometric characteristics were evaluated.